1988
DOI: 10.1159/000184993
|View full text |Cite
|
Sign up to set email alerts
|

Renal Thrombotic Microangiopathy in a Pregnant Patient with Membranoproliferative Glomerulonephritis

Abstract: Because glomerular diseases have an unforeseeable course during pregnancy, appropriate counseling is al ways compromised. Opposed evidence has been re ported without firm conclusions, and some risk factors are only considered as reference, e.g. serum creatinine (sCr) higher than 2 mg/dl, especially in the presence of severe hypertension.We report of a young female known to have membran oproliferative glomerulonephritis (MPGN) with stable renal function, controlled arterial pressure and moderate proteinuria, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…However, MPGN and HUS are pathological diagnoses, and it is entirely possible that there are common pathogenetic factors. Several reported cases of HUS complicating MPGN would seem to support this hypothesis [81][82][83].…”
Section: Factor H and Hus: The Evidencementioning
confidence: 85%
“…However, MPGN and HUS are pathological diagnoses, and it is entirely possible that there are common pathogenetic factors. Several reported cases of HUS complicating MPGN would seem to support this hypothesis [81][82][83].…”
Section: Factor H and Hus: The Evidencementioning
confidence: 85%
“…A single case (Case 2) carried a CFH genetic alteration that would have predisposed to both MPGN and to aHUS [18], but he was also found to be homozygous for the risk haplotype CFH-H3 that could have led to overt aHUS; moreover the other two cases carried respectively the CFH-H3 (in heterozygosity) and the MCPggaac (in homozigosity) aHUS-risk haplotypes, that could have genetically predisposed to aHUS. In our literature review (Table 3) [23,24,33,[48][49][50][51][52][53][54][55], we found 17 cases of aHUS associated with MPGN. Complement mutations were not investigated in the earliest reports but, by the time genetic and immunological complement analyses became available, mutations in CFH, CFI, C3, and in CFP (encoding for properdin, which stabilizes the AP C3 convertase) [56] were identified in six patients with MPGN/aHUS [33,51,54], whereas anti-CFH antibodies were found in other two patients [53,54].…”
Section: Mpgn/c3 Glomerulopathy (C3gn)mentioning
confidence: 99%